(3QSGdI aj GdCSWQdGHs - (3CHh GdbGSe GdUaGQ, CMeO Hf YHO Gddg Hf eMeO GdZGabj,J (B426 (3g` s
(3ChdgG (B:s
(3HYO GdOjHGLI (B: (3PcQ BdGJ GdGSWQdGH hGdCSeGA GdhGbYI YdjgG Chd Pdc GdMdbI s
(3BNQgG (B:s
(3aEPG aYdJ gcPG eG fXQ fbWI GdfXjQ aeG hbYJ Ydjg ef GdGSad ef GdSGYGJ s
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B104s
(3HQhcdeGf (B- (3GdLRA (B1 - (3U (B224 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B39 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdadcs